Correlation between the hydrogen chemical potential and pop-in load during in situ electrochemical nanoindentation. (November 2015) - Barnoush, Afrooz; Kheradmand, Nousha; Hajilou, Tarlan
Graphical abstract: Abstract: The variation in the pop-in load during electrochemical nanoindentation of Fe 3 wt.% Si alloy at different cathodic polarizations was measured. It is clearly shown that a higher hydrogen chemical potential results in a lower pop-in load, which is an indication of easier dislocation nucleation below the tip. Classic dislocation theory and defactant model are used to analyze the data and calculate the excess hydrogen on the dislocation line at different electrochemical potentials.